“ISSUES OF REDUCING THE PARTICIPATION OF WITNESSES BY THE WIDE INTRODUCTION OF DIGITAL TECHNOLOGIES IN CRIMINAL PROCEEDINGS” (World Bulletin of Management and Law, 2023)
The purpose of the study is to improve the system of electronic proceedings by introducing new norms into the criminal procedure legislation. At the same time, this study promotes the idea of reducing the participation of witnesses in the criminal process due to the widespread introduction of digitalization capabilities. Its scientific novelty lies in the fact that today every person in society is in the process of reforming digital technologies in one sector. The introduction of such innovations in the criminal process will not only facilitate the work of the competent authorities, but also protect the rights and interests of citizens, and contribute to protection. Therefore, this topic, analyzed based on scientific approaches, analysis of legislation and the experience of some foreign countries, is aimed at improving certain norms in criminal proceedings